Experimental Study of Red-, Green-, and Blue-Based Light Emitting Diodes Visible Light Communications for Micro-Projector Application. Issue 3 (3rd May 2016) - Chou, H.-H.; Liaw, S.-K.; Jiang, J.-S.; Teng, C.
ABSTRACT: In this research, an experimental short-range visible light communication link using red-, green-, and blue-based light-emitting diodes (LEDs) for portable micro-projector applications is presented. A Reconfigurable design of a post-equalizer aimed to improve the inherent narrow modulation bandwidth of red-, green-, and blue-based LEDs has been experimentally implemented, and its effectiveness with optical filters at the receiver is investigated. Reflective liquid-crystal-on-silicon-based micro-projection architecture, widely used in portable micro-projectors, was set up to evaluate the proposed visible light communication system. The measurement results demonstrated that a significant aggregative bandwidth improvement of 162 MHz as well as an aggregative data transmission rate of nearly 400 Mb/s can be achieved by using a non-return-to-zero–on-off keying (NRZ–OOK) modulation scheme based on only one polarization state of incident light without any offline signal processing.